2018
DOI: 10.1016/j.poly.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Refining the anchor: Optimizing the performance of cyclometallated ruthenium(II) dyes in p-type dye sensitized solar cells

Abstract: A comparison of the performances of p-type dye sensitized solar cells (DSCs) sensitized by three cyclometallated ruthenium(II) dyes differing in their anchoring domains is presented. The dyes are [Ru(bpy)2(H1)] (H31 = (4-(2phenylpyridin-4-yl)phenyl)phosphonic acid) and the salts [ n Bu4N][Ru(bpy)2(1)] and [Ru(bpy)2(H2)][PF6] (H22 = (4-(2-phenylpyridin-4-yl)phenyl)carboxylic acid). DSCs were fabricated with FTO/NiO working electrodes and either an I-/I3-/MeCN or I-/I3-/MeCN:EtCN (3:1 by volume) electrolyte. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…All cells show similar fill-factors which, although low, are typical of p-type DSCs [10]. In comparison to our earlier work in which P1 gave values of V OC in the range 82-97 mV and J SC values between 1.84 and 2.76 mA cm −2 [21][22][23], the DSCs in Table 1 with sensitizer P1 achieve significantly higher values of V OC , but lower values of J SC . We attribute the differences to a change in the method of fabrication of the working electrodes (see Section 2.3), with the use of both pre-and post-treatments with Ni(OAc) 2 [32] proving beneficial.…”
Section: Dsc Performancessupporting
confidence: 51%
See 2 more Smart Citations
“…All cells show similar fill-factors which, although low, are typical of p-type DSCs [10]. In comparison to our earlier work in which P1 gave values of V OC in the range 82-97 mV and J SC values between 1.84 and 2.76 mA cm −2 [21][22][23], the DSCs in Table 1 with sensitizer P1 achieve significantly higher values of V OC , but lower values of J SC . We attribute the differences to a change in the method of fabrication of the working electrodes (see Section 2.3), with the use of both pre-and post-treatments with Ni(OAc) 2 [32] proving beneficial.…”
Section: Dsc Performancessupporting
confidence: 51%
“…Values of R t , R rec and Q µ are derived from the individual values of r t , r rec and q µ [34][35][36] and the resistance and constant phase element of the platinum counter electrode (R CE , Q CE ). A CPE was used for charge transfer processes at both the NiO working electrode and platinum counter electrode due to the different porosity of the electrode surfaces [38]; we have previously detailed the equation used to calculate the fitted capacitance (C µ ) [21]. Table 2.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
See 1 more Smart Citation
“…maximum PCE of 0.079-0.116%. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] The performance of DSSCs using different NiO nanostructures is further evaluated by electrochemical impedance spectroscopy (EIS, Fig. 6b).…”
Section: àmentioning
confidence: 99%
“…Phosphonic acid anchoring groups have been shown to bind more strongly to semiconductor oxide surfaces than carboxylic acids and we have been particularly interested in the use of the phosphonic acid anchoring ligands shown in Scheme 1. The phosphonic acid anchor has been shown to be effective in complexes containing {Ru(bpy) 2 (CˆN)} + [11,12], {Cu(bpy) 2 } + [13,14], and {Zn(tpy) 2 } + [15,16] cores (CˆN = a cyclometallating ligand such as the conjugate base of 2-phenylpyridine, bpy = 2,2 -bipyridine), and we have demonstrated that, in copper-based dyes, the presence of both a 1,4-phenylene spacer between a bpy metal-binding domain and the phosphonic acid is beneficial to DSC performance [17]. The tpy derivative shown in Scheme 1 has been used in a number of {Ru(tpy) 2 } + -and {Zn(tpy) 2 } + -based dyes [15][16][17][18][19][20][21][22], and theoretical studies indicate that the presence of the 1,4-phenylene spacer enhances the rate of electron-transfer across the dye/semiconductor interface [23].…”
Section: Introductionmentioning
confidence: 99%